Project Planning for Improvement in a Healthcare Environment: Developing a Prioritization approach to manage patients’ access to the Urodynamics exam - Lopes Pécora, Ana Tereza; Fraga, Rogério de; Ruiz, Angel; Frega, José Roberto; Pecora Jr, Jose Eduardo (The Journal of Modern Project Management, 2022)
The first in-first out rule does not seem the most appropriated to manage the access of patients to health exams or services such as surgery. Indeed, each patient has his/her level of urgency and, furthermore the utility that each patient retires from the service differs according to several clinical but also risk and social related aspects. The decision of which patient to prioritize is tough because, in the current context where capacity is much lower than demand, choosing one patient means to delay others. Thus, this paper proposes a project methodology to prioritize patients into a Urodynamic service. The methodology, developed by a multidisciplinary team, is applied in a public hospital in Brazil, taking into consideration clinical and social criteria. We interviewed Urodynamics specialists, and a Fuzzy-AHP method is used to compute the weight of each criterion. Our preliminary results show the potential of the proposed methodology and methods, and that not only for the described case, but to other health services facing similar problems.